Disparity in the Verdict of Prosecutors Corruption Crime Case of Pinagki Sirna Malasari and Hasti Sriwahyuni in Based on the Perspective of Donald Black’s Legal Theory - Nandang, Asep; Fakrulloh, Zudan Arief (Yayasan Adra Karima Hubbi, 2024)
Indonesia is a country of law (Rechsstaat) not a country of power (Machtstaat). Therefore, it must be the Commander, the law is not a tool of the ruler or businessman, the law does not belong to the ruler or businessman, as mandated by the 5th principle of Pancasila, “Social Justice for All Indonesian People”. “Equality before the law” all are equal before the law, no discrimination is the hope of all Indonesian people. On the other hand, corruption creates social inequality, the distance between the rich and the poor is getting further, and corruption has hampered development and social welfare. Corruption will continue to grow until the justice system can punish perpetrators of crimes and keep government authority under control. When justice is “bought” or intervened politically, the people are the victims who suffer. Das solen and das sein are two very different things, the law that is aspired to, the ideal law with the reality in society, the law that should occur in society with the law that occurs in society there is a disparity. Legal discrimination is a serious obstacle in upholding justice according to the expectations of the community, the perpetrators of corruption will continue to increase and increase and will not have a deterrent effect, if there are no concrete efforts to eradicate corruption. Leaders must pay serious attention and guarantee the independence of institutions that enforce the law to eradicate corruption. Now is the right time to end impunity for corruption.